Nivel de riesgo en prácticas de campo en los estudiantes de la Facultad de Agronomía, fundo Zungarococha. Loreto 2024 - Cachay Canayo, Andy Steve (2025)
This study focuses on evaluating the level of knowledge about safety in field practices among students from the Faculty of Agronomy at the Zungarococha Farm, Loreto, 2024. Despite the importance of practical training in agricultural education, students face various risks during their activities, highlighting the need for more robust education on occupational safety. The purpose of this research was to analyze students' perception of risks in the field and the effectiveness of their safety training. A quantitative methodology was used, with surveys conducted among Agronomy and Environmental Management students, assessing their knowledge and prior experience in field activities, as well as their ability to identify risks. The results revealed that, although students demonstrated adequate knowledge of basic safety principles, key areas were identified that require reinforcement, particularly in physical injury prevention, stress management, and emergency response. Additionally, Agronomy students showed greater consistency in knowledge, while Environmental Management students excelled in areas related to environmental risk management. It is concluded that, while basic knowledge exists, it is essential to improve practical training and safety protocols in the field to reduce risks and ensure students' health during their practices.